Foraging efficiency, stocking rates, grazing pressure and livestock weight changes in the Sahel - Hiernaux, Pierre H.Y.; Ayantunde, Augustine A.; Leeuw, P.N. de; Fernández Rivera, S.; Sangare, M.; Schlecht, Eva (International Rangeland Congress, Inc., 1999)
Published and new data from experiments conducted in several range sites in Niger and Mali were analysed to assess wet season, dry season and year-round animal weight changes, stocking rates, forage availability, feed intake and faecal excretions of cattle, sheep and goats. Herbage availability over the year and wet season increased with annual rainfall and broadly determined annual stocking rate. Mean annual stocking rate across sites and grazing systems was 59 kg liveweight/ha, with a range of 15-145 kg. Animals gained weight in the 3-4 month wet season and lost weight during the 8-9 month dry season, resulting in low annual gain (0.4 g/kg per day). Dry season losses were more severe under continuous grazing systems and on wetter sites and increased with increasing grazing pressure. Animal performances were not clearly related to forage use efficiency which on average was 45<+->15 percent net (32<+->12 percent gross) over the year and up to 66<+->19 percent net (38<+->21 percent gross) in the wet season.